2021
DOI: 10.1186/s12951-021-00981-7
|View full text |Cite
|
Sign up to set email alerts
|

Self-assembled fluorescent hybrid nanoparticles-mediated collaborative lncRNA CCAT1 silencing and curcumin delivery for synchronous colorectal cancer theranostics

Abstract: Background Cancer synergistic therapy strategy in combination with therapeutic gene and small molecule drug offers the possibility to amplify anticancer efficiency. Colon cancer-associated transcript-1 (CCAT1) is a well identified oncogenic long noncoding RNA (lncRNA) exerting tumorigenic effects in a variety of cancers including colorectal cancer (CRC). Results In the present work, curcumin (Cur) and small interfering RNA targeting lncRNA CCAT1(si… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 55 publications
(40 reference statements)
0
19
0
Order By: Relevance
“…The results showed that the proportion of total apoptotic cells in HT-29 and CT-26 cells treated with Cur-LF-EGCG-HA nanoparticles was significantly higher than that of LF-EGCG-HA nanoparticles and Free Cur, indicating that the curcumin-loaded nanoparticles promoted the apoptosis of two colorectal cancer cell lines, which was consistent with the results of MTT. Researchers have reported that curcumin, in response to the expression of Bcl-2 and Caspase-3, can induce apoptosis in a variety of cancer cells, including colorectal cancer cells . Cai et al also showed that doxorubicin encapsulated in nanoparticles can enhance doxorubicin-induced cytotoxicity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results showed that the proportion of total apoptotic cells in HT-29 and CT-26 cells treated with Cur-LF-EGCG-HA nanoparticles was significantly higher than that of LF-EGCG-HA nanoparticles and Free Cur, indicating that the curcumin-loaded nanoparticles promoted the apoptosis of two colorectal cancer cell lines, which was consistent with the results of MTT. Researchers have reported that curcumin, in response to the expression of Bcl-2 and Caspase-3, can induce apoptosis in a variety of cancer cells, including colorectal cancer cells . Cai et al also showed that doxorubicin encapsulated in nanoparticles can enhance doxorubicin-induced cytotoxicity.…”
Section: Resultsmentioning
confidence: 99%
“…Researchers have reported that curcumin, in response to the expression of Bcl-2 and Caspase-3, can induce apoptosis in a variety of cancer cells, including colorectal cancer cells. 58 Cai et al 59 also showed that doxorubicin encapsulated in nanoparticles can enhance doxorubicin-induced cytotoxicity. Notably, the proportion of total apoptotic cells in HT-29 cells treated with LF-EGCG-HA nanoparticles was significantly higher than free curcumin, possibly due to the toxic effects of EGCG and LF in LF-EGCG-HA nanoparticles on HT-29 cells.…”
Section: Effect Of Nanoparticles On Apoptosis Of Ht-29 and Ct-26 Cellsmentioning
confidence: 99%
“…Furthermore, in order to silence the oncogenic activity of CCAT1 lncRNA, siCCAT1 was conjugated to polymeric hybrid nanoparticles (CSNP). In this way, it was possible to obtain a good anti-tumor effect in the HT-29 subcutaneous xenograft model of colorectal cancer [89]. Finally, by exploiting the enhanced permeability and retention (EPR) effect, Bi et al were able to deliver NPs loaded with siAFAP1-AS1 to the tumor site.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…Curcumin combined with si-MALAT1 could significantly reduce its expression and inhibit the cell activity, migration, and invasion of SW480 (colorectal cancer cell) [ 127 ]. Through polymeric hybrid nanoparticles (CSNPs), combining curcumin with siCCAT1 (Lnc CCAT1 small interfering RNA) could effectively inhibit the proliferation and migration of HT-29 cells (colorectal cancer cells) and induce a high apoptosis rate in a synergistic manner [ 128 ]. Hence, nanoparticles packaged with overexpressed/silenced Lnc RNAs and collaboratively transported with curcumin may provide a better and more promising strategy for colorectal cancer treatment.…”
Section: Curcumin and Colorectal Cancer Therapy Based On Non-coding R...mentioning
confidence: 99%